Mental well-being and coping strategies during COVID-19 pandemic : A cross-sectional study on Bangladeshi university students - Khan, Umme (My University, 2022)
The contagious COVID-19 virus classified as a pandemic by World Health Organization. In early March 2020, the virus spread in Bangladesh affected the mental well-being of the students due to the prolonged lockdown and uncertainties related academic life. This study aimed to measure the prevalence of mental health problems along with identifying determinants of mental health problems and exploring the coping mechanisms of university students to deal with mental health problems during COVID-19 pandemic. The number of respondents of this study were 138 university students who were enrolled in master’s level. The tool of data collection was self-reported questionnaire followed by a stratified sampling method. Results showed that a large number of students of this study were suffering from moderate to severe anxiety, depression, and stress (81, 61%, 40% respectively). Bandura’s self-efficacy theory (1997) align with this current study result in a sense that action of the individual influenced by particular situation and thus crisis situation like COVID-19 trigged the psychological well-being of the students. The socio-demographic determinants of this study identified that university students’ who hailed from urban areas and were not living with family during the pandemic suffered from depression. Analysing the COVID-19 related determinants result showed that students who were experiencing academic lag during COVID-19, having physical ailments for past two weeks and those who contracted COVID-19 virus were more likely to suffer from depression and anxiety. Moreover, to assess the coping strategies adopted by the students during COVID-19, the Brief-COPE (Carver, 1997) model was used. The coping mechanism adopted by the students to deal with psychological problems during COVID-19 was planning, active coping and religion which helped to decrease the depression, anxiety and stress. On the other hand, adopting the maladaptive coping strategies like substance use, behavioural disengagement, and self-blame during the pandemic likely to increase the mental health problems among the students. It is highly recommended to the concerned authority (i.e government, teachers) to come forward to ensure mental well-being among the students and taking measures on diminishing the mental health problems. In addition, introducing curriculum on mental well-being and creating open platform to discuss about mental health problems can also mitigate the issues by learning from one’s experiences.
Keywords: COVID-19, mental health, coping strategy, self-efficacy, university students